Penerapan Entrepreneur Rahmatan Lil'alamin di Unit Perekonomian Toserba Sunan Drajat - Nor Maysari; Siswadi Siswadi; Nur Maizatus Sodiah (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2022)
Today entrepreneurship activities have begun to experience a turnaround and experience a shift in business orientation, where business people begin to try to balance material and spiritual orientation. One institution that is concerned about entrepreneurship is the Islamic boarding school, in order to bring us all towards falah (success / happiness in the world and in the hereafter) with the application of Islamic methods and principles Rahmatan lil'alamin. Mursyid stated that in general, the business of pesantren is still very simple and not well organized, especially the number of pesantren that play a role in community economic empowerment has not reached 50%. This is very important to support the independence of pesantren and also as an effort to develop the entrepreneurial spirit of students in Islamic boarding schools so that they have the capital to live and have a family in the future and with such a model pesantren can be an important element to build national independence and create good students who are moral, intellectually empowered, hardworking and independent. However, there is a pesantren that has been well known for its entrepreneurial aspects, namely the Sunan Drajat Islamic Boarding School (PPSD) in Lamongan. The pesantren has various business units, both in agribusiness, manufacturing, and trade/services. While data analysis techniques are used using data education, data presentation, and conclusion drawing; The purpose of the study is to answer, know, describe and analyze the problem formulation; 1) How is the implementation of rahmatan lil'alamin-based entrepreneurship in the Sunan Drajat Department Store Economic Unit? 2) What are the factors that can support entrepreneurship in the Sunan Drajat Department Store Economic Unit? The analysis used with an approach through the relationship of the application of supporting factors for employees with entrepreneurship or entrepreneurship based on Islamic teachings. The application of department store management based on the Islamic concept of Rahmatan lil'alamin, there are several indicators with the description of rationality, Like business in general, it should do business is to seek profit for welfare. Intelligence, Determining product prices according to percentage in calculations that are not careless. Balance between heart and mind, Adjust product prices with fixed labels. As well as comprehensive, maintaining property (daily financial records are carried out which are then used as accountability reports).